Shape Memory Alloy (SMA) Damping for Smart Miniature Systems - Jacob, Kiran; Ahmadi, Shahabeddin; Shayanfard, Pejman; Wendler, Frank; Kohl, Manfred (Calm, Smooth and Smart: Novel Approaches for Influencing Vibrations by Means of Deliberately Introduced Dissipation, 2024)
Vibration damping and control using Shape Memory Alloy (SMA) foil based devices for miniature systems are presented. The high material hysteresis allows for energy dissipation up to 34 % for pseudoelastic and 86 % for one-way SMA material. Passive and active dampers are developed using SMA damper devices of single and double bridge structures and their performances are evaluated using a shock loading event. The dampers demonstrate high energy dissipation and achieve mass stabilization without any oscillation under vertical shock loading. A two-degree of freedom (2-DoF) vibration stabilization platform is developed using a monolithic SMA device, enabling ease of assembly. Operating frequencies up to 13 Hz are achieved, suitable for stabilization against vibrations in handheld devices, for eg., in smartphone cameras. Transient responses of damper devices to shock and harmonic loading are simulated based on 2D plane stress finite element models for SMA bridges, that well predict the measured mass displacement curves. The 2-DoF structures require multi-axial constitutive models that take into account the complex loading paths for spatially coupled movements.
CRIS-Team Scopus Importer:2023-10-06